2020
DOI: 10.1017/bsl.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Limit of Incompleteness I

Abstract: In this paper, we examine the limit of applicability of Gödel’s first incompleteness theorem ($\textsf {G1}$ for short). We first define the notion “$\textsf {G1}$ holds for the theory $T$”. This paper is motivated by the following question: can we find a theory with a minimal degree of interpretation for which $\textsf {G1}$ holds. To approach this question, we first examine the following question: is there a theory T such that Robinson’s $\mathbf {R}$ interprets T but T does not interpret $\mathbf {R}$ (i.e.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Arithmetical completeness theorem for GL: For any modal formula φ in L(GL), GL ⊢ φ iff PA ⊢ φ f for every arithmetic interpretation f . 14 Arithmetical completeness theorem for GLS: For any modal formula φ, GLS ⊢ φ iff N |= φ f for every arithmetic interpretation f . 15 Gödel's incompleteness theorems are closely related to paradox.…”
Section: Some Popular Misinterpretations Of Gödel's First Incompleten...mentioning
confidence: 99%
See 1 more Smart Citation
“…Arithmetical completeness theorem for GL: For any modal formula φ in L(GL), GL ⊢ φ iff PA ⊢ φ f for every arithmetic interpretation f . 14 Arithmetical completeness theorem for GLS: For any modal formula φ, GLS ⊢ φ iff N |= φ f for every arithmetic interpretation f . 15 Gödel's incompleteness theorems are closely related to paradox.…”
Section: Some Popular Misinterpretations Of Gödel's First Incompleten...mentioning
confidence: 99%
“…13 For details of the properties of Truth and Prov, we refer to [73] and [97]. 14 GL is a modal system consisting of the following schemes of axiom: (1) all tautologies;…”
Section: Some Popular Misinterpretations Of Gödel's First Incompleten...mentioning
confidence: 99%
“…T means S is interpretable in T but it is unknown whether S interprets T follows from the idea behind the proof of Theorem 4.7 of [2] that the interpretability degrees of computably enumerable essentially undecidable theories have infima. Hence, if there exists a minimal essentially undecidable theory, then that theory is also the minimum essentially undecidable theory.…”
mentioning
confidence: 99%
“…In [7], Jeřábek shows that there is an essentially undecidable theory that is interpretable in R but that does not interpret R. The theory Jeřábek gives is such that all partially recursive functions are representable. In Section 3 of [2], Yong Cheng uses results in [7] to give many examples of essentially undecidable theories that are interpretable in R but that do not interpret R. One of the referees observed that the existence of theories strictly below R w.r.t. interpretability also follows from the work of Shoenfield [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation